2011
DOI: 10.1094/pdis-07-10-0552
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Soybean Rust in Soybean Sentinel Plots in Florida

Abstract: Young, H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Early application of a fungicide when the pathogen has not yet established leads to waste, while when a fungicide is applied too late, yield losses are likely to occur due to disease development. Sentinel plots have been successfully used in the USA in a national network system aimed at monitoring the appearance of soybean rust (Geisler et al, 2007;Young et al, 2011). The sentinel plots are used to detect soybean rust already present at low densities and are established in multiple locations in the soybean growing regions.…”
Section: Soybean Rust Control Strategies and Current Researchmentioning
confidence: 99%
“…Early application of a fungicide when the pathogen has not yet established leads to waste, while when a fungicide is applied too late, yield losses are likely to occur due to disease development. Sentinel plots have been successfully used in the USA in a national network system aimed at monitoring the appearance of soybean rust (Geisler et al, 2007;Young et al, 2011). The sentinel plots are used to detect soybean rust already present at low densities and are established in multiple locations in the soybean growing regions.…”
Section: Soybean Rust Control Strategies and Current Researchmentioning
confidence: 99%
“…), an introduced perennial legume estimated to cover up to 7 million acres in the southern United States (Jurick et al, 2008). Nevertheless, the ability of P. pachyrhizi to reproduce rapidly, spread quickly, and severely defoliate soybean plants when environmental conditions are favorable makes SBR a potentially serious economic threat, especially in growing seasons with above-average rainfall (Young et al, 2011). Marchetti et al (1976) reported that while urediniospore germination occurs between 10.0 and 28.5°C, the optimal range is 15 to 25°C.…”
mentioning
confidence: 99%
“…Approximately half of 125 kudzu plants grown from seed collected from 56 geographically distinct locations in Kentucky, Louisiana, Mississippi, and North Carolina and inoculated with three isolates of P. pachyrhizi produced an RB lesion type (Bonde et al 2009). Additional studies showed that a considerable proportion of the kudzu in Florida is either immune (18%) or resistant (32%) (Jordan et al 2010;Young et al 2011b). Furthermore, in the majority of instances where multiple plants from a site were tested, each plant reacted similarly to three isolates of P. pachyrhizi (Bonde et al 2009).…”
Section: Epidemiologymentioning
confidence: 99%
“…Although kudzu provides the initial inoculum for epidemics on soybean, the rapid increase in disease prevalence on kudzu toward the end of the season may be driven, in part, by inoculum produced on soybean (Christiano and Scherm 2007;Young et al 2011b). In addition, analyses of soybean rust epidemics from 2005 to 2011 showed a strong association between initial and final epidemic spread (Mundt et al 2015); and the epidemics from 2005 to 2008 correlated a location's infection history (i.e., the previous number of years infected with soybean) to the previous year's incidence of soybean rust (Young et al 2011b).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation